The diabetic foot syndrome - Piaggesi, Alberto; Apelqvist, Jan (Basel : Karger, 2018)
In recent years, "diabetic foot" has become the common name given to chronic complications of diabetes mellitus in the lower limb. This book provides an up-to-date picture of the clinical scenario, the latest understanding of the mechanisms in regard to pathology, the current standards of therapy, and the organizational tasks that a modern approach to such a complex pathology warrants. All contributors have delivered articles that are as informative and straight-to-the point as possible, including not only their own experience in the field, but also giving a wider picture to link each article to the other. The Diabetic Foot Syndrome is not only relevant to specialists, but also to all the caregivers involved in the management of the patients at risk for developing the pathology, those affected, and those who are at risk of recurrences.
Keywords: PIE DIABÉTICO; DIABETES MELLITUS -- COMPLICACIONES; PIE DIABÉTICO -- COMPLICACIONES; PIE DIABÉTICO -- TRATAMIENTO; PIE DIABETICO -- CIRUGÍA